1958
DOI: 10.1136/hrt.20.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension in Congenital Heart Disease

Abstract: An important group of congenital cardiovascular defects is that characterized by the presence of an arterio-venous shunt, of which atrial septal defect, ventricular septal defect, and patent ductus arteriosus are common examples. In these the flow of blood is generally directed from left to right so that cyanosis is absent, but some may ultimately develop cyanosis (cyanose tardive) following a reversal of the shunt. Cardiac catheterization may then show the pressure in the pulmonary artery to be raised to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
3

Year Published

1960
1960
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 39 publications
0
4
0
3
Order By: Relevance
“…21 PAH is usually defined as the following: (1) mean pulmonary artery pressure of 25 mm Hg or greater and (2) either pulmonary capillary wedge pressure (PCWP) of 15 mm Hg or less or left ventricular end-diastolic pressure (LVEDP) of 15 mm Hg or less or measured left atrial pressure of less than 15 mm Hg and (3) PVR of 3 Wood units or greater. 22 It is inherent from these definitions that right heart catheterization is an essential test for the diagnosis of PAH.…”
Section: Definition and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…21 PAH is usually defined as the following: (1) mean pulmonary artery pressure of 25 mm Hg or greater and (2) either pulmonary capillary wedge pressure (PCWP) of 15 mm Hg or less or left ventricular end-diastolic pressure (LVEDP) of 15 mm Hg or less or measured left atrial pressure of less than 15 mm Hg and (3) PVR of 3 Wood units or greater. 22 It is inherent from these definitions that right heart catheterization is an essential test for the diagnosis of PAH.…”
Section: Definition and Classificationmentioning
confidence: 99%
“…1 Multiple studies have since expanded our understanding of the syndrome to include other congenital heart defects. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] CHD is one of the world's leading birth defects and pulmonary arterial hypertension (PAH) associated with CHD is one of the most common causes of morbidity and mortality in this group of patients. 20 …”
Section: Introductionmentioning
confidence: 99%
“…Dauer und Intensität des Hochdruckes bestimmen den Zeitpunkt, wann die Phase der funktionellen Adaptation in die der morphologisch faßbaren Veränderungen übergeht (SCHOENMACKERS [26]). EVANS [11] fandbei seinen Untersuchungen, daß die Veränderungen an den Gefäßwänden sich glichen, unabhängig davon, wo der Sitz des Defektes lag oder ob eine sog. essentielle pulmonale Hypertonie bestand.…”
unclassified
“…Different opinions are held concerning the reversibility of the pulmonary hypertension in ventricular septal defect with a raised pulmonary vascular resistance. Thus Evans and Short (1958) thought it to be due to permanent structural changes, Burchell (1959) stated that acetylcholine caused a slight decrease in pressure in only 1 of 3 cases, Swan and Wood and Marshall, (1957) found that breathing 100per cent oxygen failed to produce a fall in pressure in some cases. Wood (1958) reported that acetylcholine did not produce a fall in pressure in the Eisenmenger syndrome.…”
mentioning
confidence: 99%